GLOCALIZATION OF ENGLISH LEARNING IN THE GENERATION Z COMMUNITIES AMONG ENGLISH LEARNERS IN SOLO CITY - Linda Safitri (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
This research discusses the phenomenon of the glocalization of Generation Z in learning English among English learners especially in Solo city. The effect of globalization for Gen Z where they were born and grow along with the development of technology. The purpose of this research was to find out and understanding the glocalization of English learning in the generation Z communities among English learners in Solo city. The approach used was a quantitative approach with a descriptive method. The data collection technique used were observation, interviews, documentation study, with data collection tools in the form of observation, questioner, interview, and documentation. Research findings showed that the glocalization of technological developments is very influential for genertion Z in shaping self- identity in this era. It can be seen from the English learners in Solo city did not leaving the mother language although learning a foreign language. Based on the observations, interviews and documentations that the researcher carried out that through the inovation of technology can make the emotional closeness created by the learners and will be able to compete and introduce their local culture to the international world. From the result of the research that the glocalization of learning English still need to improved by balancing the use of global languages and local languages. Like as learning English use local culture. So that, in the future it is expected that there will be internationalization of local Indonesian culture.